Strain-induced piezotronic effects in nano-sized GaN thin films. (October 2021) - Puneetha, Peddathimula; Mallem, Siva Pratap Reddy; Lee, Young-Woong; Lee, Jung-Hee; Shim, Jaesool
Abstract: Flexible devices have attracted considerable attention because of their very productive applications in the diverse areas such as healthcare, artificial intelligence, and robotics. Accordingly, in this study, we fabricated a flexible nano-sized GaN thin-film device via a double-transfer method using a laser lift-off process from sapphire with thermal tape and then with carbon tape onto a polycarbonate substrate. With the application of compressive/tensile strains, the flexible nano-sized GaN thin-film device can be mechanically controlled by the piezotronic effect. The device has excellent electromechanical performance with a gauge factor of 2206 at a compressive strain of 0.32%, which is nearly 11.11 times greater than that of a conventional strain-gauge value. Furthermore, the device shows an effective ON condition in the compressive direction and OFF condition in the tensile direction at an applied bias voltage of 0.5 V. The fabricated device has potential for innovative and advanced applications such as human–machine interfaces, biomedical diagnoses, prostheses, intelligently controlled rooms, and active flexible electronics. Graphical Abstract: The flexible nano-sized GaN thin-film device can be mechanically controlled by compressive/tensile directions based on the piezotronic effect. The device has excellent electromechanical performance with a gauge factor of 2206 at a compressive strain of 0.32%, which is nearly 11.11 times greater than that of a conventional strain-gauge value. ga1 Highlights: Used nano-sized GaN thin film device via a double-transfer method. Mechanically controlled by compressive/tensile directions based on the piezotronic effect. The device shows 11.11 times greater than that of a conventional value. This piezotronic device allows a way for future flexible device applications.